The Antimicrobial Effect of Alcoholic Extract of Peganumharmala L Seeds on Clinically Isolated Gram Negative and Gram Positive Bacteria - Dh. Al-Haidari, Alaa M.; M. Hasan, Jinan (Iraqi Journal of Science, 2023)
The aim of the present study was assess the antimicrobial effect ofPeganumharmala L seeds extracts by ethanol (80%) on gram negative and grampositive bacteria and four concentrations (25, 50, 75 and 100) mg/ml were prepared.Four clinical isolates of bacteria were used; two were positive and two werenegative bacteria; that include: Bacillus, Staphylococcus aureus, Pseudomonasaeruginosa and Escherichia coli. The results showed that all concentration that havebeen used had antimicrobial effect against gram negative and gram positive bacteriaand the best concentration that have the best antimicrobial effect was 100 mg/ml andthe effect of alcoholic extraction was greater on gram positive bacteria than gramnegative bacteria, also the antimicrobial effect of two antibiotics were tested onthese four clinical isolates these antibiotics are imipeneme and gentamycin. Theeffect of imipeneme was greater than the effect of gentamycin also the effect ofimipeneme on gram positive bacteria was greater than on gram negative bacteria.The synergistic effect of alcoholic extraction of PeganumharmalaL seeds andantibiotics was studied and the result show that the antimicrobial effect of antibiotics(imipeneme and gentamycin) was increased when these antibiotics discs weresaturated with 100mg/ml of seeds extracts. The Minimal Inhibitory Concentration(MIC) and Minimal Bactericidal Concentration (MBC) of the alcoholic extracts ofPeganumharmala L seeds on these four clinical isolates were tested and the resultshow that the MIC was: for Bacillus : 3.12 mg/ml , Staphylococcus aureus:1.56mg/ml, Pseudomonas aeruginosa: 6.25 mg/ml and Escherichia coli:3.12 mg/ml) andthe MBC was :( for Bacillus : 3.12 mg/ml , Staphylococcus aureus:3.12 mg/ml,Pseudomonas aeruginosa: 12.5 mg/ml and Escherichia coli: 6.25 mg/ml.